Toxoplasmosis in HIV/AIDS patients: a current situation - Nissapatorn, V.; Lee, C.; Quek, K.F.; Leong, C.L.; Mahmud, R.; Abdullah, K.A. (2004)
The seroprevalence of toxoplasmosis among 505 of human immunodeficiency virus (HIV)/AIDS patients was 226 (44.8; 95 CI 42.64-51.76): 27 (47.4) and 199 (44.4) showed Toxoplasma seropositivity with and without toxoplasmic encephalitis (TE), respectively (P<0.05). The majority of these patients were in the 25-34 age group (44 versus 39), male (86 versus 76), and Chinese (49 versus 53), though no statistical significance was found between the two. Significant differences between these two groups were noted, however, in terms of marital status, occupation, and present address. The heterosexual exhibited the most frequent behavior at risk for HIV infection, and accounted for 51 and 59 of patients with and without TE, respectively. Only 17/260 (6.5) and 1/137 (0.7) of them later acquired TE after receiving primary chemoprophylaxis (cotrimoxazole) and antiretroviral therapy including HAART (P<0.05). Fifty-seven (11.3) out of those 505 patients were diagnosed with AIDS-related TE. The most common clinical manifestation was headache (56). The computed tomography scan findings showed most lesions to be multiple (96.4), hypodense (66.7), and in the parietal region (39.3). Twenty-seven (47.4) patients had chronic (latent) Toxoplasma infection as evidenced by seropositivity for anti-Toxoplasma (IgG) antibody. At the time of diagnosis, the range of CD4 cell count was from 0-239 with a median of 25 cells/cumm. We also found that a CD4 count of less than 100 cells/cumm was significantly associated with development of TE (P<0.05). Clinical outcomes showed that among those who survived, 21 (36.8), 16 (28.1), and 2 (3.5) of patients had completed treatment, transferred out, and were lost to follow up, respectively. Unfortunately, 18 (31.6) of the cases were officially pronounced dead. Overall, 7 (12.3) patients were detected as recurrent TE in this study.